2018
DOI: 10.1007/s00109-018-1726-6
|View full text |Cite
|
Sign up to set email alerts
|

Treprostinil reduces endothelial damage in murine sinusoidal obstruction syndrome

Abstract: Sinusoidal obstruction syndrome (SOS) is a major complication after hematopoietic stem cell transplantation and belongs to a group of diseases increasingly identified as transplant-related systemic endothelial disease. Administration of defibrotide affords some protection against SOS, but the effect is modest. Hence, there is unmet medical need justifying the preclinical search for alternative approaches. Prostaglandins exert protective actions on endothelial cells of various vascular beds. Here, we explored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…So far there are three drugs in this group: treprostinil, iloprost, and selexipag, which have been used in treatment of PAH with similar results as epoprostenol, which was expected, considering that they have the identical mechanism of action, even though they can stimulate adenylyl cyclase and reduce cell cytoplasmic calcium levels through different groups of receptors [65] , [66] , [67] . There is research reporting endothelium protection by Treprostinil, however, there is lack of studies investigating the effectiveness of epoprostenol analogues in treatment of ARDS [68] . Therefore, it is hard to assess the potential of treprostinil, iloprost or selexipag in treatment of COVID-19 associated lung injury but it should be corresponding to that of eporostenol.…”
Section: Prostanoidsmentioning
confidence: 99%
“…So far there are three drugs in this group: treprostinil, iloprost, and selexipag, which have been used in treatment of PAH with similar results as epoprostenol, which was expected, considering that they have the identical mechanism of action, even though they can stimulate adenylyl cyclase and reduce cell cytoplasmic calcium levels through different groups of receptors [65] , [66] , [67] . There is research reporting endothelium protection by Treprostinil, however, there is lack of studies investigating the effectiveness of epoprostenol analogues in treatment of ARDS [68] . Therefore, it is hard to assess the potential of treprostinil, iloprost or selexipag in treatment of COVID-19 associated lung injury but it should be corresponding to that of eporostenol.…”
Section: Prostanoidsmentioning
confidence: 99%
“…Another recent study suggested that the presence of Gs-coupled prostanoid receptors in liver sinusoidal endothelial cells was responsible for the beneficial effect of prostaglandins. In fact, treprostinil binds and activates EP 2 , EP 4 , and IP receptors, resulting in attenuation of ischemia-induced hepatic cell injury[ 101 ].…”
Section: Introductionmentioning
confidence: 99%